Order Flow and Liquidity around NYSE Trading Halts - Corwin, Shane A.; Lipson, Marc L. (Journal of Finance, 2000)
We study order flow and liquidity around NYSE trading halts. We find that market and limit order submissions and cancellations increase significantly during trading halts, that a large proportion of the limit order book at the reopen is composed of orders submitted during the halt, and that the market‐clearing price at the reopen is a good predictor of future prices. Depth near the quotes is unusually low around trading halts, though specialists and/or floor traders appear to provide additional liquidity at these times. Finally, specialists appear to “spread the quote” prior to imbalance halts to convey information to market participants.